Optimization of Wastewater Treatment Plant Design using Process Dynamic Simulation: A Case Study from Kurdistan, Iraq - Issa, Hayder M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
Satisfactory effluent characteristics are indispensable to evaluate the performance of any wastewater treatment plant (WWTP) design. Dynamic simulation software has a great role in pursuing this objective, in which an efficient and cost-effective design is constantly performed. In this study, a dynamic simulator sewage treatment operation analysis over time (STOAT) has been used under certain influent conditions to optimize design possibilities for modifying an existing primary WWTP College of Engineering Wastewater Treatment Plant (COEWWTP) at Erbil, Kurdistan, Iraq. The optimization was established on the basis of total suspended solids (TSS) and biochemical oxygen demand (BOD) characteristics in the effluent. Two alternative design schemes were proposed; trickling biofilter and aeration basin. In the dynamic simulation for the investigated design schemes, the predicted effluent profile showed that each of the existing and trickling biofilter processes has failed to correspond to the valid effluent limitation, whereas predicted results of the aeration basin exhibited an effluent profile that meets TSS and BOD allowable limits. Different simulation models have been implemented by STOAT to simulate treatment processes in studied design approaches: ASAL 1 model; BOD model; BOD semi-dynamic model; and SSED 1 model. This study offers an additional understanding of WWTP design and facilitates the application of dynamic simulators as tools for wastewater treatment development in Kurdistan.